A Pedology of Agricultural Land of Shemiranat Regions, Iran - Najmi, Simin; Arzjani, Zahra (International Journal of Bio-resource and Stress Management, 2011)
Studies on territorial resources, land’s coverage (vegetative and edaphic) and land capability in Shemiranat region are the in recognizing the area. Here, information has been gathered on different soil types. soil’s elevation, gradient, type, origin etc using available data from different recognized sources as well as map using GIS software. It’s the attempt to determine the valuation of territorial resources, the land capability for yearly agricultural handling and range management in forestry.